Family firms and corporate governance rating : the Greek case - Xanthakis, M; Tsipouri, LJ.; Spanos, L. (Culturally-sensitive models of family business in Eastern Europe: a compendium using the globe paradigm, 2008)
Recent studies argue that the spread-adjusted Taylor rule (STR), which includes a response to the credit spread, replicates monetary policy in the United State. We show (1) STR is a theoretically optimal monetary policy under heterogeneous loan interest rate contracts in both discretionay and commitment monetary policies, (2) however, the optimal response to the credit spread is ambiguous given the financial market structure in theoretically derived STR, and (3) there, a commitment policy is effective in narrowing the credit spread when the central bank hits the zero lower bound constraint of the policy rate.